PERBEDAAN MOTIVASI KERJA GURU TAMAN KANAK-KANAK YANG TERAKREDITASI DAN BELUM TERAKREDITASI DI KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU - Hersi Puspika Ria; Wusono Indarto; Nurlita Nurlita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRAKThe purpose of this research is to find out if there is significant motivational difference between accredited and unaccredited teachers who work in kindergarten in Kecamatan Marpoyan Damai Kota Pekanbaru. This is a comparative research writer limited the problem in this research based on accreditation. Writer used likert scale, and collect the data using questionaire. Population in this research is accredited and unaccredited kindergarten teachers in Kecamatan Marpoyan Damai Kota Pekanbaru. The total number is 187 teachers. To choose sample, writer used random sampling, means that writer choose the sample randomly, without lookin at the stratum. The total number is 65 teachers. Variables in this research are, X1: motivation of accredited teachers and X2: motivation of unaccredited teachers. Result shows that there is the difference. It can be seen from t hitung, which is bigger than t tabel (3.43>2.65).So Ho is rejected and Ha is accepted. Writer concluded that there is significant motivational difference between accredited and unaccredited kindergarten teachers in Kecamatan Marpoyan Damai Kota Pekanbaru.Keywork : work motivation